Application of Design Thinking in Designing User Interface Prototype of Worker Health Screening Application at PT Petrokimia Gresik - Ramadani, Deo Globy; Tranggono, Tranggono; Islami , Mega Cattleya Prameswari Anissa (Journal La Multiapp, 2025)
The application of digital technology in the worker health screening process is an important need in the industrial work environment, especially in supporting the effectiveness and efficiency of the OHS medical team's work. This research aims to design a user interface for the AppSheet-based worker health screening application using the Design Thinking approach. This method was chosen because it is centered on user needs and is able to produce innovative solutions through the stages of Empathize, Define, Ideate, Prototype, and Testing. Data collection was conducted through interviews and observations of five respondents from the OHS medical team and five department representatives. Assessment of the design was carried out using the usability testing method, with efficiency, effectiveness, and System Usability Scale (SUS) parameters. The results showed that the Design Thinking approach was able to produce an application interface that meets user needs, improves understanding of workflows, and minimizes recording errors. The developed application not only supports the digital health evaluation process, but also has the potential to reduce administrative burden and improve the quality of medical services at PT Petrokimia Gresik.